Impact analysis of quality award process on learning organizations - Altay, Pelin Gözde. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
The core competency of the most e®ective organizations is their capacity to learn in an increasingly complex and unpredictable business environment. Assessors play an additional critical role in the Quality Award Process by contributing in their own personal development and in transformation of their organization into a learning organization. This study has two purposes. First, it aims to explore the individual and orga- nizational learning of the assessors obtained throughout the Quality Award Process. To do so, a survey is carried out to aid management to realize the contribution of this process to the individuals working as assessors. It is clearly observed that assessors ben- e歔t from the award process as an e®ective learning platform. Hence, the organizations should encourage and support their employees to act as assessors for being individually developed and for getting organizational learning by utilizing their experiences. The second purpose of this study is to develop an instrument to assess the current status of the organizations as being learning organizations. Five organizations are selected, and a survey is carried out to investigate strengths and weaknesses regarding the learning organization characteristics. The result of this study indicates that selected organizations exhibit many characteristics of a learning organization with particular strengths in \Organizational Formation" and \IT Infrastructure" and weaknesses in \Empowerment" and \Learning from Failures and Successes". This study shows that applying for the Quality Award Process and acting as an assessor in this process have substantial impacts on individual and organizational learning.
Keywords: Total quality management.; Organizational learning.